Development of a Module Based on Problem Based Learning (PBL) Model And Local Potential As Supporting Biodiversity Materials In Senior High School of SMA Negeri 1 Natal - Amelisa Putri; Kartika Manalu (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
One of the learning resources for biology is biodiversity. Region-specific biodiversity differs. Thus, in light of biodiversity, many students still struggle to comprehend the material covered in biology lectures, particularly at SMA Negeri 1 Natal.The research uses the ADDIE model research and development (R&D) method. The instrument of this research is a questionnaire sheet for material experts, media experts, teachers and students to test practicality and pre-test and post-test to test effectiveness. Class X MIPA-1 SMA Negeri 1 Natal students as test subjects. Testing was carried out on 30 students and biology teachers to see the practicality of the module using student and biology teacher response questionnaires. Based on the validation results from material experts, a percentage of 96.25% was obtained with the criteria "Very Valid". The validation results from media experts obtained a result of 81.2% with the criteria "Very Valid". The results of the teacher's response to the module were 87.7% for the "Very Practical" criteria. The results of student responses to the module obtained a percentage of 93.5% with the criteria "Very Practical". And the effectiveness results were 77.4% with effective criteria. Thus, biology learning modules based on problem based learning and local potential modules on biodiversity material are very practical and effective for teachers and students to use in biology learning